Social research methods : for students and scholars of theology and religious studies - Iyadurai, Joshua (Chennai, India. Marina Centre for Interdisciplinary Studies in Religion., 2023)
This book demystifies designing and conducting qualitative, quantitative, and mixed methods research with scientific rigor. Social Research Methods, benefits researchers from theology and religious studies in designing interdisciplinary research and interacting with social sciences and other disciplines to study contextually relevant issues by focusing on lived religion, lived theology, lived experience, and real-world problems. Joshua Iyadurai skillfully guides researchers with a step-by-step guide on the practical nuances of choosing a topic, engaging literature, selecting a paradigm, collecting and analyzing data, interpreting the findings, and writing a research proposal and a dissertation/thesis/article for qualitative, quantitative, and mixed methods research. A separate chapter on supervising and examining social research helps students and professors to understand each other's role in field-based studies. Social Research Methods is an indispensable resource for researchers from theology and religious studies and a valuable practical guide for researchers from social sciences and humanities
Keywords: Research Methods.-- Theology and Religious Studies; Social Research; Research Methodology